BUDAYA MERANTAU PEREMPUAN MINANGKABAU (Studi Pada Pedagang Perempuan Minangkabau di Pasar Kemiri Muka Beji Kota Depok Provinsi Jawa Barat) - Oktaviani, Rizka (Studi Budaya Nusantara, 2022)
This study aims to: (1) identify the reasons behind the tradition of migration among Minangkabau women in Kemiri Muka Market, Beji, Depok City, West Java Province; and (2) examine the dynamics of the matrilineal system experienced by Minangkabau women traders in Kemiri Muka Market, Beji, Depok City, West Java Province, during migration. This research employs a qualitative method, with data collection techniques including observation, interviews, and documentation. The findings reveal that: (1) the push factors driving Minangkabau women to migrate are economic and educational needs, while the pull factors include easier access to education, better income and employment opportunities, and encouragement from family members—such as siblings or husbands—who had migrated earlier. (2) The dynamics of the matrilineal system in relation to the preservation, safeguarding, and management of ancestral property change when Minangkabau women migrate. After migration, the status of traditional assets—such as the rumah gadang (traditional house), fields, and rice paddies—undergoes transformation. The rumah gadang, which historically served not only as a physical residence but also as a cultural symbol, has shifted in function and is now often inhabited by sons, even though it is traditionally reserved for daughters. Likewise, fields and plantations are now managed by male descendants, and rice paddies are handled solely by family members who remain in the village. When Minangkabau women choose to migrate, they no longer fulfill their traditional role as daughters in preserving, safeguarding, and managing ancestral property.